2016
DOI: 10.1167/iovs.16-19212
|View full text |Cite
|
Sign up to set email alerts
|

Lack of R-Ras Leads to Increased Vascular Permeability in Ischemic Retinopathy

Abstract: PurposeThe role of R-Ras in retinal angiogenesis and vascular permeability was evaluated in an oxygen-induced retinopathy (OIR) model using R-Ras knockout (KO) mice and in human diabetic neovascular membranes.MethodsMice deficient for R-Ras and their wild-type (WT) littermates were subjected to 75% oxygen from postnatal day 7 (P7) to P12 and then returned to room air. At P17 retinal vascularization was examined from whole mounts, and retinal vascular permeability was studied using Miles assay. Real-time RT-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 55 publications
0
44
0
Order By: Relevance
“…One of the important functions of R-Ras is to enhance the blood vessel wall integrity and reduce blood leakage by stabilizing VE-cadherin at the endothelial adherens junction (2, 10). In the current study, we showed compelling evidence that cAMP is a negative regulator of R-Ras expression.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the important functions of R-Ras is to enhance the blood vessel wall integrity and reduce blood leakage by stabilizing VE-cadherin at the endothelial adherens junction (2, 10). In the current study, we showed compelling evidence that cAMP is a negative regulator of R-Ras expression.…”
Section: Resultsmentioning
confidence: 99%
“…A strong down-regulation of R-Ras is associated with leaky blood vessels in human malignant tumors and diabetic retinopathy (2, 10). In this study, we demonstrated that the activation of cAMP signaling results in CREB3-dependent down-regulation of RRAS in both macrovascular and microvascular ECs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations